SUMBANGAN METODE AZAMI OLEH ISMAIL FAHMI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QURAN ANAK USIA DINI - Jauharotun Nafi’ah; Achmad Kurniawan Pasmadi (As-Sulthan Journal of Education, 2025)
Azami method is one of the methods of learning to read the Qur'an. Ismail Fahmi is a teacher who is recognized as the initiator of the Azami method. By providing fun learning to read the Qur'an in accordance with the development of children. This paper aims to examine the contribution of the Azami method in improving the ability to read the Qur'an of early childhood. The contributions provided by the Azami method include; 1) Significant improvement in children's ability to read the Qur'an; 2) A fun and effective method; 3) Development of cognitive and motor skills. This paper is compiled using a qualitative descriptive method. Data were taken from interviews with the head of Rumah Quran Kids, journals, and books on the ability to read the Qur'an of early childhood. This study is expected to be a reference for teachers in learning the Qur'an in order to foster students' interest and motivation in studying the Qur'an using fun methods and in accordance with children's development.